Mechanism of KMT5B haploinsufficiency in neurodevelopment in humans and mice - Sheppard, Sarah E.; Bryant, Laura; Wickramasekara, Rochelle N.; Vaccaro, Courtney; Robertson, Brynn; Hallgren, Jodi; Hulen, Jason; Watson, Cynthia J.; Faundes, Victor; Duffourd, Yannis; Lee, Pearl; Celeste Simon, M.; et al. (Science Advances, 2023)
Pathogenic variants in KMT5B, a lysine methyltransferase, are associated with global developmental delay, macrocephaly, autism, and congenital anomalies (OMIM# 617788). Given the relatively recent discovery of this disorder, it has not been fully characterized. Deep phenotyping of the largest (n = 43) patient cohort to date identified that hypotonia and congenital heart defects are prominent features that were previously not associated with this syndrome. Both missense variants and putative loss-of-function variants resulted in slow growth in patient-derived cell lines. KMT5B homozygous knockout mice were smaller in size than their wild-type littermates but did not have significantly smaller brains, suggesting relative macrocephaly, also noted as a prominent clinical feature. RNA sequencing of patient lymphoblasts and Kmt5b haploinsufficient mouse brains identified differentially expressed pathways associated with nervous system development and function including axon guidance signaling. Overall, we identified additional pathogenic variants and clinical features in KMT5Brelated neurodevelopmental disorder and provide insights into the molecular mechanisms of the disorder using multiple model systems.
CRIS-Team Scopus Importer:2023-03-24